Attitudes and motivation in the treatment of IPV : a case study of two intimately violent men - Nuutinen, Noora (2017)
This case study used qualitative content analysis to examine the cases of two intimately violent men. Both participated in a group intervention but experienced dramatically different outcomes. In the case of "Henri", the intervention was especially successful, but in the case of "Mikael" it was unsuccessful. The data of this study consisted of the video tapes of the men’s therapy sessions, and of the interviews of their spouses. The research questions were the following: 1) Were there changes in the men’s attitudes toward a) women, b) masculinity and c) violent behavior?, 2) How high was the men’s motivation for treatment and making changes in themselves? and 3) Did their attitudes and motivation differ from one another?